Analysis of Herpes Simplex Virus ICP0 Promoter Function in Sensory Neurons during Acute Infection, Establishment of Latency, and Reactivation In Vivo - Thompson, R. L. (American Society for Microbiology, 2003)
We have begun an analysis of the functional architecture of the ICP0 promoter in neurons in vivo with the ultimate goal of determining how this gene is regulated during reactivation in vivo. Promoter/reporter mutants in which the Escherichia coli beta-galactosidase (β-Gal) gene was driven by various permutations of the ICP0 promoter were employed to permit the analysis of promoter function without the added complications that would arise due to inappropriate regulation of ICP0 protein levels. A whole-ganglion immunohistochemical staining procedure (N. M. Sawtell, J. Virol. 77:4127-4138, 2003) was used for direct comparisons of the expression of the promoter/reporter gene to expression of the native protein in the same cell. In this way, the expression of the putative wild-type promoter could be validated and results for mutant promoters could be compared to expression of the native gene. We found that a DNA fragment from bp −562 through the methionine start codon of the ICP0 gene contained all sequences required for properly regulated ICP0 expression in diverse cell types (including sensory neurons of the trigeminal ganglia [TG]) in vitro and in vivo, as indicated by colocalization of ICP0 and β-Gal. Truncation of the ICP0 promoter to bp −145 or −129 resulted in the loss of immediate-early (α) kinetics. The truncated promoters expressed high levels of the reporter gene with leaky late (γ1) kinetics in vitro and in some cell types in vivo. Unexpectedly, the truncated promoters did not express in TG neurons. Thus, TAATGARAT or other sequences upstream of bp −145 in the ICP0 promoter are required for basal expression of ICP0 in neurons but are not required for basal expression in other cells in vivo. There was a >95% concordance between reporter and native protein expression detected with the 562-bp promoter in neurons during the acute stage. However, this was not the case during reactivation from latency in vivo, as nearly twice as many neurons contained detectable β-Gal as contained detectable ICP0. This same 562-bp promoter/reporter cassette, when placed in the context of a latency-associated transcript (LAT) null mutant, resulted in >95% concordance of expression of β-Gal and ICP0 during reactivation in vivo. These last results strongly suggest that there is a posttranscriptional constraint on the expression of ICP0 protein during reactivation from latency and that this constraint is mediated by LAT.